SIMULATION MODEL OF THE ASSIGNMENT TO SUPPORT OF SEA OPERATIONS IN COMMAND OF THE FLEET II - Agus Tri Haryanto; Suparno Suparno; I Made Jiwa Astika (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Scheduling of Indonesian Warship Assignment is Operation Presence at sea by Indonesian Warship to carry out security duties at sea based on time. Security threats and violations at sea in the form of theft of fish, timber and other natural resources and violations of territorial boundaries by foreign vessels require the presence of Indonesian Warship for security.The limited number of Indonesian Warship and the budget provided by the state as well as the need for securing the vast sea area of ​​the Republic of Indonesia in the need for thought about the Indonesian warship assignment model.The purpose of this research is to get the best alternative in order to optimize the scheduling of the Indonesian Warship assignment plan in order to produce a ship movement schedule in this case made by SOPS.Indonesian Warship is used in modeling as many as 52 Indonesian Warship to 17 operating sectors .This method of scheduling research attempts to develop an optimization model by applying the Integer Linear-Zero One Programming method.by identifying decision variables, establishing objective functions and identifying constraints. The results of the assignment model simulation in the form of the composition of Indonesian Warship assignment to 17 operating sectors with a maximum coverage area reached is 65,130,362.68, scheduling Indonesian Warship assignments carried out over a period of 1 year, there is also an increase in Coverage Area of ​​12.16% from real conditions.Simulation of this assignment model can be used as a consideration in the decision making of the TNI Al Leadership about the assignment of Indonesian Warship in the operations sector, so that it can be implemented / applied in the future. Keywords: The Fleet Command II (Koarmada II), Indonesian Warship, ILP-Zero One Programming